A physically based, one-dimensional three-fluid model for direct contact condensation of steam jets in flowing water. (March 2017) - Heinze, David; Schulenberg, Thomas; Behnke, Lars
Highlights: We present a simulation model for the condensation of steam jets in flowing water. Condensation at the jet interface is modeled based on the surface renewal theory. Correlations for stratified two-phase flows are adapted to condensing steam jets. The dependency of the jet length on the water flow rate is qualitatively predicted. Abstract: A simulation model for the direct contact condensation of steam jets in flowing water is presented. In contrast to previous empirical approaches, the model takes into account the underlying physical phenomena governing the condensation process. Condensation at the interface between the steam jet and the surrounding water is calculated according to the surface renewal theory. Entrainment of water into the steam jet is modeled based on the Kelvin–Helmholtz and Rayleigh–Taylor instability theories. The resulting steam-water two-phase flow is simulated based on a one-dimensional three-fluid model. An interfacial area transport equation is used to track changes of the interfacial area density due to droplet entrainment and steam condensation on droplets. The simulation results are in good qualitative agreement with published experimental data. In particular, the dependency of the steam jet length on the flow Reynolds number is properly reproduced. This corroborates our theory that the heat transfer coefficient at the interface of a condensing steam jet can be linked to the water flow rate via the interfacial friction factor.